Heat transfer enhancement of biomass based stirling engine - Nik Abdul Rahman, Nik Kechik Mujahidah; Saadon, Syamimi; Che Man, Mohd Hasrizam (Semarak Ilmu Publishing, 2022)
Stirling engine as an external combustion engine with high efficiencies and able to use any types of heat source is the best candidate to recover waste heat of the exhausted gas by converting it into power. Thus, in this study Stirling engine was introduced to evaluate the possibility of recovering waste heat from biomass to produce power. For this reason, Computational Fluid Dynamic (CFD) simulation test was performed to design an initial computational model of Stirling engine for low temperature heat waste recovery. The CFD model was validated with the experiment model and shows 6.11% of average deviation. This result proves that the computational model can be further used to evaluate the performance of Stirling engine as waste heat recovery of biomass-based industrial boilers for low-grade temperature heat source.